Parenting styles, gender roles, and academic burnout among Chinese students: a cultural perspective - Wang, Yundi; Ma’rof, Aini Marina; Sulong, Rose Manisah (Human Resource Management Academic Research Society, 2024)
Academic burnout among Chinese students is particularly severe due to a unique mix of cultural, educational, and family pressures. The strong emphasis placed on academic achievement and high family expectations intensifies this issue. While research on academic burnout is expanding, most studies have focused on Western contexts and often overlook cultural factors specific to China, such as the influence of parenting styles, societal expectations, and gender roles. This study introduces a conceptual framework that explores how Chinese cultural values impact students' burnout, with a particular focus on parenting styles and gender norms. It highlights how traditional values related to family honor and academic success shape parenting approaches, which, in turn, affect students' mental well-being. The research also investigates how societal expectations tied to gender roles contribute to differing levels of academic stress and burnout between boys and girls. By evaluating the effects of authoritative, authoritarian, and permissive parenting styles while considering gender as a moderating factor, this framework offers important insights into the dynamics of burnout within Chinese culture.